2022
DOI: 10.1186/s12906-022-03690-2
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Evaluation of Sequentially extracted Leaf of Vernonia auriculifera Hiern (Rejicho)

Abstract: Background Though there are reports about V. auriculifera antimicrobial activity, there is not enough information about its activity on some bacterial and fungal species. Besides, there was no quantitative evaluation done for phytochemicals previously. Therefore, the main purpose of this research work is to evaluate the antimicrobial activity and quantitative evaluation of the phenol and flavonoid contents of V. auriculifera. Objectives The objecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…It means that in this study, methanol was more efficient at extracting phytochemicals of plants than ethanol. This is consistent with what was reported in previous research, which demonstrated that the yield of some plants, such as A. mangium leaf extract, M. pudica aerial parts, and Vernonia auriculifera Hiern leaves, was the greatest when it was extracted in a polar solvent [ 46 – 48 ]. However, the result of the fractionation yield of M. pudica in this study revealed that even though n-hexane is the lowest polarity solvent, it was associated with the highest yield.…”
Section: Discussionsupporting
confidence: 93%
“…It means that in this study, methanol was more efficient at extracting phytochemicals of plants than ethanol. This is consistent with what was reported in previous research, which demonstrated that the yield of some plants, such as A. mangium leaf extract, M. pudica aerial parts, and Vernonia auriculifera Hiern leaves, was the greatest when it was extracted in a polar solvent [ 46 – 48 ]. However, the result of the fractionation yield of M. pudica in this study revealed that even though n-hexane is the lowest polarity solvent, it was associated with the highest yield.…”
Section: Discussionsupporting
confidence: 93%
“…Phenols are compounds that are polar so their solubility is highest in polar solvents. Polar solvents can dissolve phenols better so that their levels in the extract become high [29,52].…”
Section: Resultsmentioning
confidence: 99%
“… 11 It can be found in humid lowland forests, wooded grassland, and scrub at elevations between 1600 and 2800 m in Ethiopia’s southwest and south, where it is widely dispersed. 12 Various Vernonia species are used to manage many diseases in Ethiopian traditional medicine. Experimental research on a variety of Vernonia species has also revealed a plethora of activities, including anti-plasmodial, analgesic, anti-inflammatory, antimicrobial, antidiabetic, antioxidant, and anticancer.…”
Section: Introductionmentioning
confidence: 99%